2003
DOI: 10.1200/jco.2003.01.143
|View full text |Cite
|
Sign up to set email alerts
|

Phase I Trial of Preoperative Concurrent Doxorubicin and Radiation Therapy, Surgical Resection, and Intraoperative Electron-Beam Radiation Therapy for Patients With Localized Retroperitoneal Sarcoma

Abstract: Preoperative chemoradiation, surgical resection, and EB-IORT are feasible for patients with RPS. Preoperative external-beam radiation can be administered to a total dose of 50.4 Gy with continuous-infusion doxorubicin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
1
2

Year Published

2005
2005
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 141 publications
(64 citation statements)
references
References 15 publications
1
60
1
2
Order By: Relevance
“…In addition, studies often mix up different groups of patients. [17][18][19][20][21][22][23][24][25] Therefore, most guidelines for clinical practice are based on phase 2 studies and historic comparisons. This emphasizes the importance of predictive and prognostic factors.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, studies often mix up different groups of patients. [17][18][19][20][21][22][23][24][25] Therefore, most guidelines for clinical practice are based on phase 2 studies and historic comparisons. This emphasizes the importance of predictive and prognostic factors.…”
Section: Discussionmentioning
confidence: 99%
“…There have been several pilot or phase I studies utilizing idoxuridine-or doxorubicin-based chemoradiation [27][28][29].…”
Section: Combined Chemotherapy and Radiation Therapymentioning
confidence: 99%
“…It has been shown that RT reduces the likelihood of local recurrence, but it has not been shown that RT provides a definite survival benefit. [12][13][14][15][16] A problem asso- ciated with adjuvant RT is that the dose is limited by the tolerance of the surrounding normal tissues, primarily the small bowel, to 45-50 grays (Gy) over 5 weeks. It has been shown that these doses are effective in extremity sarcomas when they are administered preoperatively but are lower than doses traditionally administered postoperatively (60 -65 Gy over 6 -7 weeks).…”
Section: Treatmentmentioning
confidence: 99%